The Effect of Leverage, Liquidity, Profitability, Coverage, Growth, and Firm Size With Auditor’s Reputation As A Moderating To Bond Rating of Banking Firm - VEGA M. ROSA; MUSDHOLIFAH MUSDHOLIFAH (Fakultas Ekonomi dan Bisnis Universitas Padjadjaran, 2016)
This research aims to determine the effect of leverage, liquidity, profitability, coverage, and firm size with auditor’s reputation as a moderating to bond rating of banking firm which listed in Indonesia Stock Exchange (BEI) and rated by PT Pefindo period 2004 to 2013. In this research the sample were 176 bond which issued by banking firms. The sampling technique is using purposive sampling method, whereas the method of analysis used logistic regression analysis. This research shows that profitability, growth, and firm size have an effect on bond rating. In the other hand, leverage,liquidity, and coverage have no effect on bond rating. Meanwhile auditor’s reputation as a moderation variable did not affect to strengthening or weakening the effect between profitability and bond rating.